Problems of Health of Buffaloes Reared in Swampy Area in South Kalimantan - ., Suhardono (Indonesian Bulletin of Animal and Veterinary Sciences, 2000)
The population of buffaloes reared in swampy area in the province of South Kalimantan is high, and show a very good condition. These animals, however, are fulnerable to several diseases. From the analysis of available data and of a field monitoring, some diseases are potential to occur at certain time of the year, such as clostridium, surra, and fasciolosis. The emergence of the diseases in this area associates with some factors, such as availability of water, weed (enceng gondok or Eichornia crassipes), vector/intermediate host (flies and snails), and reservoir host (deer and wild pig). The tide water in this swampy area influences the population of vectors/intermediate hosts, also provide a condition for a contact between buffaloes and the reservoir hosts when seeking for drinking water. Deterioration of the weed and grasses facilitate an ideal media for propagation of anaerobic bacteria (e.g: clostridium). Based on these characteristics of those factors it is highly suspected that during the dry season, before the lowest water tide, the transmission of parasitic diseases in buffaloes (Fasciolosis and Trypanosomiasis) is occuring, while for clostridial disease is transmitted during the high water tide. Â  Key word: Buffalo, fasciolosis, trypanosomiasis, clostridium, swampy habitat